Distribuicão do estresse gerado por forças axiais ou oblíquas sobre implantes transmaxilar horizontal e cone morse acoplados a diferentes modelos protéticos - Lowry Neto, Guilherme Walter (2019)
The objective was to evaluate the stress distribution generated by axial or oblique loads on horizontal transmaxillary (HTM) and morse tapper (MTa) implants coupled to prosthetic models through photoelastic analysis. 14 specimens from the HTM group and 14 from the MTa group were made with 3 different prosthetic models. The axial or oblique loads of 200 and 400N were applied in cantilever and to the center of the bar. The stress distribution was calculated by the magenta area using the Photoshop and ImageJ software’s. Two statistical tests were applied (ANOVA and Tukey) (α = 0.05). In the first analysis, the variables considered were: implant type, direction and load position. For second analysis: loading position, type of implant and prosthesis. When compared the implants type, the MTa group had a higher stress distribution under 200N in axial cantilever, oblique cantilever and centralized oblique (p <0.05) and for 400N in oblique cantilever and centralized oblique (p <0.05). When the load direction was compared, the stress distribution was higher when axial loads were applied (p <0.05). In the HTM group (400N) the axial loads had higher stress distribution (p <0.05). In the MTa group (400N) the distribution was higher at axial-cantilever load than the oblique-centralized load (p <0.05). There was no statistical difference regarding the position of the load and prosthetic models (p> 0.05). It can be concluded that the HTM group had a lower stress distribution than the MTa. It’s use may be justified by the need for a lower vertical bone height.